Optimal treatment for post-MI heart failure in rats: dapagliflozin first, adding sacubitril-valsartan 2 weeks later - Tao, Wenqi; Yang, Xiaoyu; Zhang, Qing; Bi, Shuli; Yao, Zhuhua (Frontiers in Cardiovascular Medicine, 2023)
Background Based on previous research, both dapagliflozin (DAPA) and sacubitril-valsartan (S/V) improve the prognosis of patients with heart failure (HF). Our study aims to investigate whether the early initiation of DAPA or the combination of DAPA with S/V in different orders would exert a greater protective effect on heart function than that of S/V alone in post-myocardial infarction HF (post-MI HF). Methods Rats were randomized into six groups: (A) Sham; (B) MI; (C) MI + S/V (1st d); (D) MI + DAPA (1st d); (E) MI + S/V (1st d) + DAPA (14th d); (F) MI + DAPA (1st d) + S/V (14th d). The MI model was established in rats via surgical ligation of the left anterior descending coronary artery. Histology, Western blotting, RNA-seq, and other approaches were used to explore the optimal treatment to preserve the heart function in post-MI HF. A daily dose of 1 mg/kg DAPA and 68 mg/kg S/V was administered. Results The results of our study revealed that DAPA or S/V substantially improved the cardiac structure and function. DAPA and S/V monotherapy resulted in comparable reduction in infarct size, fibrosis, myocardium hypertrophy, and apoptosis. The administration of DAPA followed by S/V results in a superior improvement in heart function in rats with post-MI HF than those in other treatment groups. The administration of DAPA following S/V did not result in any additional improvement in heart function as compared to S/V monotherapy in rats with post-MI HF. Our findings further suggest that the combination of DAPA and S/V should not be administered within 3 days after acute myocardial infarction (AMI), as it resulted in a considerable increase in mortality. Our RNA-Seq data revealed that DAPA treatment after AMI altered the expression of genes related to myocardial mitochondrial biogenesis and oxidative phosphorylation. Conclusions Our study revealed no notable difference in the cardioprotective effects of singular DAPA or S/V in rats with post-MI HF. Based on our preclinical investigation, the most effective treatment strategy for post-MI HF is the administration of DAPA during the 2 weeks, followed by the addition of S/V to DAPA later. Conversely, adopting a therapeutic scheme whereby S/V was administered first, followed by later addition of DAPA, failed to further improve the cardiac function compared to S/V monotherapy.